Konsep Restorative Justice Dalam Penanganan Tindak Pidana Cyberbullying Di Indonesia - Febri Bachtiar Irawan; Siti Marwiyah; Bachrul Amiq (CV. Ulil Albab Corp, 2026)
This study examines the concept of restorative justice as an alternative approach to addressing cyberbullying crimes within the Indonesian criminal justice system. The rapid development of information technology has significantly transformed social interactions, while simultaneously giving rise to cyberbullying as a form of psychological violence conducted through digital media. Conventional criminal justice mechanisms that emphasize retributive punishment are often considered insufficient to address the complex social and psychological impacts experienced by victims. This research employs a normative legal research method using statutory and conceptual approaches by analyzing relevant laws, legal doctrines, and scholarly literature. The findings indicate that restorative justice has obtained normative recognition within the Indonesian legal framework through several regulations, including the Juvenile Criminal Justice System Law (Law No. 11 of 2012), National Police Regulation No. 6 of 2019, and Prosecutor Regulation No. 15 of 2020 concerning termination of prosecution based on restorative justice. Therefore, restorative justice offers a more holistic and constructive approach that emphasizes victim recovery, offender accountability, and the restoration of social harmony. This study recommends the development of specific legal regulations governing restorative justice in cybercrime cases and strengthening the capacity of law enforcement officials in digital technology and restorative mediation.